“Where I was reduced to the condition of an animal”: the Ahu Penitentiary narrated from within by Abel Hamvultando (Curitiba, 1909-1917) (Tempo e Argumento, 2025)
In this article was analyzed a collection of texts written by journalist and poet Abel Hamvultando, who was sentenced to 29 years in prison for the murder of João Bleggi in August 1900, in Curitiba, the capital of the state of Paraná, South of Brazil. The collection includes a series of nine anonymously published articles in the newspaper O Fluminense from Niterói, a long letter addressed to the ministers of the Supreme Federal Court, and a letter signed by his mother, published in the Curitiba newspaper Diário da Tarde. The intention is to understand the variations and strategies employed by Hamvultando in a prison environment, where conditions for writing are restrictive, text circulation is limited, and freedom is constantly monitored. Despite the rigors and difficulties, the texts produced by Abel Hamvultando reveal, beyond his own experiences, perspectives on prison life that differ from those present in more official discourse and sources. In the case of Curitiba, these texts represent a unique source, given the lack of similar documentation for that period. As with so many other institutions, the memory and testimony of prisoners, and their preservation, are rare. In this sense, reading this collection of texts offers a glimpse into alternative perspectives on the history of prisons, imprisonment, and prisoners in Paraná.
Keywords: penitentiary; prisoners; letters; press